Injury illustrated : how medical images win legal cases - Gough, R. Annie (Rachael Annie) (Boca Raton, FL : CRC Press, 2021)
"Medical-Legal Illustration tackles how and why attorneys win cases utilizing medical illustrators. This is the first book on medical-legal illustration and provides an understanding of anatomy, surgical cases, and how medical illustration can clearly and succinctly illustrate accidents, medical malpractice, and death investigation for forensic use in court. Medical illustrators are trained to summarize complex facts clearly and accurately, just as lawyers eliminating complex terms utilize visuals to present clear and compelling evidence.Seemingly very different professions, the visual artist solves countless problems for the injury attorney, defining their client's injuries, and summarizing complex medical records. Medical illustrators are the ideal partners for injury attorneys needing both better understand and articulate medical conditions, injuries, and malpractice in such criminal and civil cases. The book is divided into five section which detail who medical illustrators are, what they do, the services they can provide to attorneys, and the myriad benefits of involving illustrators in cases. Artists, animators, lawyers, medical students, law students, forensic scientists, medical professionals and students will benefit to learn how this unusual career path can illuminate complex concepts to benefit legal proceedings"--
Dominos, warning : graphic images -- The brief, the reason, and reasoning -- You're grounded, growing up with anatomy -- Suspicious minds, seeking the truth -- Bunny suit, a background in forensics -- Disgusta, medical illustration master's degree -- Stars are born, products of our professors -- Sutured together, learning surgery -- History of the association, foundations of medical art and law -- Pantyhose, inside the law firm -- Message in a bottle, a settlement brochure -- Hondas, profits over people -- The Process, draw by hand -- Wile E. Coyote, real people -- Tin Cans, voluminous records -- Can't Trust a Photo, but request them all -- Interpreting Radiology, images establish facts -- Radiology is not enough, the jury needs clarification -- Netflix, the jury wants TV -- Muddy Waters, aberrant anatomy -- Healing trauma, the client is better -- Bad facts, the client is a stripper -- No facts, the lawyer didn't ask -- Pre-trial panic, last minute animations -- Six Degrees of Separation, experts & animators -- Boutique feel, not just a product but a service -- It's not rocket science, narrating brain surgery -- Headless Horseman, the value of the client likeness -- Defending doctors, medical malpractice defense -- Deep pockets, what will this cost -- MVP, minimum viable product -- Pancakes, food analogies -- Out of the box, creative alternatives -- Power tools, anything it takes -- Holograms, advances in technology -- Exhibit hall, building connections -- The wall, between our warm hearts and our dark minds -- Gross, the specter versus the science -- Pin the tail on the donkey, to show or not to show the genitalia -- Perfect data, a picture is worth a thousand words.
OCLC-licensed vendor bibliographic record.
Keywords: Medical jurisprudence; Evidence, Expert; Personal injuries; Imaging systems in medicine -- Evaluation; LAW / Medical Law & Legislation; LAW / Forensic Science